2018
DOI: 10.3389/fneur.2018.00045
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Dysfunctions in Sudden Sensorineural Hearing Loss: A Systematic Review and Meta-analysis

Abstract: BackgroundSudden sensorineural hearing loss (SSHL) not only involves cochlear function but might also be accompanied by vestibular disturbances. The assessment of vestibular function could be of great relevance in SSHL.ObjectiveTo investigate the prevalence of vestibulocochlear lesions in SSHL and the correlation of specific vestibular organs with hearing prognosis.Data sourcesA complete literature search of eligible studies in the PubMed and EMBASE databases was performed.Study selectionFor our aim, studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 40 publications
5
30
1
8
Order By: Relevance
“…There are no previous reports which explain this phenomenon yet. Current evidence however shows that ISSNHL patients with vertigo had a higher risk of vestibular organ lesions 30 and that this may be negatively associated with hearing recovery 31 . Therefore, ISSNHL patients with vertigo have a worse prognosis and we emphasize the importance of immediate and comprehensive treatments, such as medical treatments and vestibular rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…There are no previous reports which explain this phenomenon yet. Current evidence however shows that ISSNHL patients with vertigo had a higher risk of vestibular organ lesions 30 and that this may be negatively associated with hearing recovery 31 . Therefore, ISSNHL patients with vertigo have a worse prognosis and we emphasize the importance of immediate and comprehensive treatments, such as medical treatments and vestibular rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis evaluating vestibular function in SSNHL, vestibular organs were found to be involved in SSNHL regardless of the presence of vertigo, indicating that vertigo might not be an independent and determining factor. Vestibulocochlear lesion patterns showed that the utricle, followed by the LSCC, was the most susceptible to damage in SSNHL, and abnormal caloric response was a negative prognostic marker [7].…”
Section: Discussionmentioning
confidence: 98%
“…Vestibular involvement in SSNHL is hypothesized as an extension of the disease caused by the anatomical proximity and correlation of the cochlea and vestibule [6]. Recently, vestibular diagnostic methods have been included in the general evaluation of SSNHL patients, such as the caloric test, cervical vestibular-evoked myogenic potential (c-VEMP), and ocular VEMP (o-VEMP) [7]. The caloric test is a method for investigating lateral semicircular canal (LSCC) function and superior vestibular integrity, the c-VEMP can be used for assessing saccular function and the inferior vestibular pathway, and the o-VEMP can be used for evaluating utricular function and the superior vestibular pathway [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Vestibular dysfunction, commonly complained by patients as vertigo, dizziness, or lateropulsion, has been considered as a risk factor of profound hearing loss and poor prognosis [30][31][32][33][34]. Recently, researchers made their efforts to specify the lesion patterns of the vestibular system in ISSNHL and proposed that the utricle and superior vestibular pathway is the most vulnerable vestibular site in ISSNHL, followed by the lateral semicircular canal and superior vestibular pathway [30].…”
Section: Discussionmentioning
confidence: 99%